Garlic supplementation attenuates cycling exercise-induced oxidative inflammation but fails to improve time trial performance in healthy adults - Jung-Piao Tsao; Jeffrey R. Bernard; Tse-Hsin Tu; Hsiu-Chen Hsu; Chia-Chen Chang; Su-Fen Liao; I-Shiung Cheng (Taylor & Francis Group, 2023)
BACKGROUND Garlic extract has been shown to enhance antioxidant and anti-inflammation activities in humans. The present study investigated the effects of garlic supplementation on 40-km cycling time trial performance, exercise-induced oxidative stress, and inflammatory responses in healthy adults. METHODS Eleven healthy males were recruited to perform this single-blind crossover study. Participants were randomly assigned to either garlic (garlic extracts 1000 mg/d for 4 weeks) or placebo trials. Following 4-wks of supplementation, participants performed a 40-km cycling challenge. Total cycling performance time and respiratory exchange ratio (RER) were recorded. Blood samples were collected every 10 km to determine exercise-induced oxidative stress, inflammation, and muscle damage. RESULTS The 40-km cycling time trial performance was not improved following 4 weeks of garlic supplementation. However, 4-wk garlic supplementation significantly increased whole-body antioxidant capacity (total antioxidant capacity, TAC), and subsequently attenuated MDA, TNF-α, and LDH during the 40-km cycling exercise period (p < 0.05). There were no significant differences among the blood biomarkers glucose, NEFA, IL-6, UA, and CK respectively. The respiratory exchange ratio was similar between garlic and placebo trials. CONCLUSION Four-week oral garlic supplementation attenuates exercise-induced oxidative inflammation and muscle damage during a 40-km bout of cycling. However, it appeared that 4-wk oral garlic had no ergogenic effect on cycling performance in healthy males.